2018
DOI: 10.3390/bios8020038
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic and Microscopic Analysis for Monitoring Renal Osteodystrophy Signatures

Abstract: Defining the pathogenesis of renal osteodystrophy (ROD) and its treatment efficacy are difficult, since many factors potentially affect bone quality. In this study, confocal Raman microscopy and parallel statistical analysis were used to identify differences in bone composition between healthy and ROD bone tissues through direct visualization of three main compositional parametric ratios, namely, calcium content, mineral-to-matrix, and carbonate-to-matrix. Besides the substantially lower values found in ROD sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…HiPCO SWCNT (HR32-009) were obtained from NanoIntegris (Boisbriand, QC, Canada) and purified by a previously reported method [46]. Anhydrous calcium chloride (CaCl 2 ) was obtained from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…HiPCO SWCNT (HR32-009) were obtained from NanoIntegris (Boisbriand, QC, Canada) and purified by a previously reported method [46]. Anhydrous calcium chloride (CaCl 2 ) was obtained from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Another indicator of bone remodeling is the carbonate-to-matrix ratio describing the evolution of carbonate minerals relative to amide I from the collagen matrix. Its significantly higher value in the newly formed bone tissue with a high standard deviation could also be explained by carbonate substitution and different remodeling stages [52].…”
Section: Evolution Of the Bone Mineral Compositionmentioning
confidence: 99%
“…Thus, the newly formed bone is composed of less mineral relative to matrix components, indicating lower mineralization and potential bone tissue maturation in process at the BII [33-35, 39, 54, 55]. Eventually, the mineral-to-matrix ν2PO4 3-/Amide III ratio, an indicator of calcium content [52], has lower values in newly formed bone tissue, as previously observed for bone maturation [56], bone healing [34], and osseointegration of a 3D printed titanium implant [39].…”
Section: Immature Organic Phase Within Newly Formed Bonementioning
confidence: 99%
“…Whereas both spectroscopic techniques provide a comprehensive chemical analysis that is useful for understanding likelihood of fractures and is complementary to that from QCT and MRI, relating to potentially in vivo translation, Raman spectroscopy is superior due to its insensitivity to water absorption. However, despites their accessibility, there are only relatively few reports on such Raman studies [15][16][17][18][19][20][21][22][23][24][25], with a slightly larger number of FT-IR investigations [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent Raman spectroscopic study, we demonstrated that the bone samples of patients with ROD exhibit an overall increase in phenylalanine and decreases in calcium content, in mineral to matrix ratio, and in carbonate to matrix ratio [25]. Since just a single Raman spectrum is clearly not sufficient to assess at statistically significant levels the differences between normal and ROD samples, we took advantage of confocal Raman microscopy.…”
Section: Introductionmentioning
confidence: 99%